The Influence of CSR and Financial Performance in Explaining Cumulative Abnormal Return - M. Karya Satya Azhar; Adduha Annaba; Ibnu Austrindanney Sina Azhar (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study examines the influence of corporate social responsibility, leverage, earnings per share, and profitability (net profit margin and return on equity) on cumulative abnormal return. Using a quantitative approach, this study employs secondary data from 77 consumer cyclical companies listed on the Indonesia Stock Exchange during the 2019–2022 period, resulting in 308 firm-year observations selected through purposive sampling. Panel data regression analysis is conducted using EViews. The empirical results indicate that CSR and net profit margin have a positive and significant effect on cumulative abnormal return, suggesting that social responsibility disclosure and operational profitability enhance investor confidence and market reactions. In contrast, leverage and ROE show a significant negative effect on cumulative abnormal return, implying that higher financial risk and extreme equity Return may be perceived unfavorably by investors. Meanwhile, EPS does not exhibit a significant influence on cumulative abnormal return. These findings imply that both financial performance and non-financial information, particularly CSR, play an important role in shaping investor behavior, and thus should be carefully managed and transparently disclosed to strengthen market responses.